2016
DOI: 10.1055/s-0036-1584530
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Pulmonary Agenesis: A Rare and Unexpected Finding in a Newborn

Abstract: Background  Bilateral pulmonary agenesis is a rare congenital anomaly incompatible with life that can be missed on routine prenatal screening. Prenatal ultrasound diagnosis of this fatal anomaly can aid in prenatal counseling and postdelivery care.Case Study  We report the case of a newborn who was born prematurely at 29 weeks gestation and underwent several unsuccessful intubation attempts immediately after delivery.Conclusion  Autopsy examination revealed bilateral pulmonary agenesis with a short, blindly en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
3
0
2
Order By: Relevance
“…Suspicion on BPA is usually done by ultrasound examination and diagnosis made by MRI in the second and the third trimester of pregnancy [11]. Unfortunately, it is not rare that BPA can be missed on routine prenatal screening [2]. As BPA is incompatible with extrauterine life, there is a need to make a reliable diagnosis in pregnancy at the earliest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Suspicion on BPA is usually done by ultrasound examination and diagnosis made by MRI in the second and the third trimester of pregnancy [11]. Unfortunately, it is not rare that BPA can be missed on routine prenatal screening [2]. As BPA is incompatible with extrauterine life, there is a need to make a reliable diagnosis in pregnancy at the earliest.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital lung malformations can be identified in the immediate birth period or in early childhood; however, they can be diagnosed incidentally on routine imaging or autopsy [1]. Bilateral pulmonary agenesis (BPA) is a very rare congenital lung malformation incompatible with extra-uterine life [2]. BPA is usually suspected during a prenatal US scan and diagnosed by fetal MRI, in the second and third trimesters [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Esta condición consiste en la ausencia de bronquios, parénquima y vasculatura pulmonar 2,7,10,13,14 , pudiendo ser unilateral o bilateral 7,15 , siendo la primera mas frecuente, la agenesia derecha se asocia a mayores complicaciones 7 , defectos cardiovasculares (14%), musculoesqueléticos (12%), gastrointestinales, (14%) genitourinarios (9%), vasculares (9%). Puede aparecer de forma aislada o hacer parte de una entidad clínica como por ejemplo, sín-drome de Goldenhar, asociación VACTER, síndrome por microdeleción 22q11, síndrome de Holt-Oram y síndrome de Opitz G 1,4,6,[9][10][11][12]16 .…”
Section: Discussionunclassified
“…Uno de los casos reportados de agenesia pulmonar bilateral fue una paciente prematura de 29 semanas, con ecografía prenatal dentro de limites normales, que nace sin esfuerzo respiratorio y en el que no se logra intubación endotraqueal por vía aérea difícil. La paciente falleció a los 26 min y en la necropsia se documentó agenesia pulmonar bilateral con tráquea de 1 cm blindada al final, una condición incompatible con la vida 15 .…”
Section: Discussionunclassified
“…85,87 This is relevant for the study of human CDH, as there have been a few reported cases of pulmonary agenesis in humans that have intact diaphragms. 86,[88][89][90] Although genetics can account for only a small percentage of CDH cases in humans, seminal studies analyzing genes like COUP-TFII (NR2F2) have suggested that screening and genetic status should be considered when performing a differential diagnosis of CDH. 91 Integrating genetic data and the lessons learned from animal models of CDH has provided many insights into the pathways that are disrupted in CDH and is a crucial step in translating novel therapies from bench to bedside.…”
Section: Genetic Modelsmentioning
confidence: 99%